The development of the reflecion during youth (Actual Problems of Psychology in Educational Institutions, 2021)
The article consistently explores the problem of the developmentof reflection, its principles, considers various aspects of reflection. Scientificsources, works of famous scientists and psychologists are analyzed,qualitative opinions and conclusions are given. The level of developmentof reflection in young people, their desire for deep thinking, self-study,approach to the analysis of their actions and the ability to exerciseself-knowledge are shown. The results of the study are presented, the mainfeatures that characterize the level of development of reflexive thinkingin adolescence are highlighted. Conclusions are made on the basis ofinformation from scientific works and own research, which summarize theinformation about the essence of reflection at this age.
Keywords: reflection, self-knowledge, existential reflection, personal reflection